Več- in raznojezičnost v predšolskem obdobju (University of Maribor Press, 2022)
Multilingualism and Plurilingualism in the Preschool Period. Through the perspectives of various actors and the analysis of factors and elements of teaching, the monograph sheds light on the development of multilingualism in the preschool period. Individual articles cover: outlines of possibilities for developing multilingualism in kindergartens, competencies for teaching foreign languages ​​in the preschool period, preschool teachers’ attitudes towards early foreign language learning and multilingualism, attitudes and experiences of teachers with additional training for early teaching, experiencing foreign language lessons by children, parents’ views on language learning in kindergarten and work in foreign languages ​​with immigrant children. Furthermore, the monograph provides an analysis of the work in the kindergarten and an analysis of multilingual picture books. The monograph concludes with an analysis of work in a bilingual kindergarten and research into the issue of elitism in kindergarten. The monograph is intended for various target groups, and we also want to show that it is necessary to change the curriculum for kindergartens and the introduction of compulsory foreign language learning. The necessity of changing the curriculum is justified by analyzing and researching from the point of view of various target groups and positioning in the broader context of the European Union’s language policy.